2014
DOI: 10.1016/j.juro.2013.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Followup of a Large Cohort of Patients with Ovotesticular Disorder of Sex Development

Abstract: Male gender assignment was more prevalent. Long-term followup revealed adequate pubertal development and sexual activity. Complications involving the urethra developed frequently in male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 20 publications
3
37
1
7
Order By: Relevance
“…This has been a constant finding in previously published studies and can be explained by genetic, environmental, and embryological factors [19]. As in previous studies, we found that gonadal combinations were variable and unpredictable [12]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This has been a constant finding in previously published studies and can be explained by genetic, environmental, and embryological factors [19]. As in previous studies, we found that gonadal combinations were variable and unpredictable [12]. …”
Section: Discussionsupporting
confidence: 81%
“…Several retrospective studies have reported on the long-term outcomes of subjects with OT DSD [10-12]. However, there are limited studies on the clinical features, gender assignment, and treatment outcomes in children with OT DSD in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The location of the urethral meatus and associated surgical challenges, dysgenetic testicular tissue and the presence of a uterus and normal ovarian tissue influenced the assignment in the past [86]. Case studies report gender dysphoria and/or patient-initiated gender change in either direction in patients [87,88]. For this condition and others, only systematic large long-term gender outcome and QoL data will constitute a solid empirical basis for determining crucial factors involved in assignment decisions.…”
Section: Evolving Perceptions: Male or Female Assignment Reassignmenmentioning
confidence: 99%
“…Some clinicians are particularly influenced in their gender decisions by the location of the urethral meatus and the associated surgical challenges [66], while others are led to favor female assignment by the frequent presence of a uterus and normal ovarian tissue as compared to the more frequently dysgenetic testicular tissue [67]. It is not surprising, therefore, that a number of case reports show gender dysphoria and/or patient-initiated gender change in either direction in patients with ovotesticular syndrome [68,69]. Only systematic long-term follow-up data on gender outcome and quality of life in sizeable samples will constitute a solid empirical basis for deciding on the crucial factors to consider in gender assignment decisions.…”
Section: Changes In Gender Assignment Policies For Newborns With Genimentioning
confidence: 99%